A survey on optimization-based approaches to Dynamic Centralized Group Key management - An, Le Thi Hoai; Trinh, Nguyễn Thị Tuyết (Journal of Science and Technology on Information security, 2023)
Abstract—In secure multicast communication, only authorized group members are able to receive the transmitted data. Key generation, distribution, and management are all carried out by a single entity (called the Key Server) in the centralized system. The main challenges of a dynamic centralized group key management scheme include scalability overhead, rekeying overhead, storage overhead, maintaining forward and backward secrecy, etc. Logical Key Hierarchy (LKH), one of the key management methods, uses a tree structure to manage keys to share with participants. Due to the fact that members may join or exit the group at any time during communication, a crucial problem in centralized group key management (CGKM) is minimizing rekeying costs while maintaining a balanced tree. The majority of CGKM methods effectively update the group key by modifying cryptographic techniques or based on logical/heuristic arguments. One of the efficient approaches is based on an optimization model with the two mentioned important objectives. In this paper, we conduct a survey on optimization-based approaches to dynamic CGKM, which can be divided into two categories based on logical/heuristic arguments and a rigorous mathematical optimization model.